1999
DOI: 10.1007/s000110050507
|View full text |Cite
|
Sign up to set email alerts
|

Histamine release during the induction of anesthesia with propofol in allergic patients: A comparison with the induction of anesthesia using midazolam-ketamine

Abstract: Propofol was found to show a similar incidence of histamine release during the induction of anesthesia using midazolam-ketamine, and thus was also found to be a useful induction agent against histamine release for patients with a history of allergy when hydroxizine was used as a premedication.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0
1

Year Published

2001
2001
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 56 publications
0
12
0
1
Order By: Relevance
“…However, bronchospastic episodes and other reactions following propofol administration have been documented [1,[4][5][6][7][8][9][10][11][12][13][14]. Previously proposed etiologies for propofol reactions include a phenomenon related to histamine release as well as a reactionary cascade secondary to various chemical compounds found in propofol [5][6][7]. While propofol is considered to be safe, newer manufacturing of propofol, as disclosed below, can compromise its safety owing to its preservative or formulation [1].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, bronchospastic episodes and other reactions following propofol administration have been documented [1,[4][5][6][7][8][9][10][11][12][13][14]. Previously proposed etiologies for propofol reactions include a phenomenon related to histamine release as well as a reactionary cascade secondary to various chemical compounds found in propofol [5][6][7]. While propofol is considered to be safe, newer manufacturing of propofol, as disclosed below, can compromise its safety owing to its preservative or formulation [1].…”
Section: Discussionmentioning
confidence: 99%
“…However, cardiorespiratory responses were typically seen after bolus dosing versus that of a slow infusion [1,11]. Reactions, when present, may manifest as pruritus with hives, flushing, swelling, bronchconstriction, wheezing, dyspnea, nausea, stomach cramps, hypotension, cyanosis, diaphoresis, shock, and loss of consciousness [4,6,7,10]. As a whole, exacerbations are more likely to occur in chronic asthmatic patients with reactions of a bronchoconstrictive nature more commonly seen in steroid-dependent asthmatics [4].…”
Section: Discussionmentioning
confidence: 99%
“…Anesthetics such as propofol and thiopental are rare causes of anaphylaxis as well (11, 12). Other agents used in the operating room that may provoke an immune response include midazolam, ketamine, chlorhexidine, colloids, protamine sulfate, and local anesthetics such as lidocaine (11).…”
Section: Discussionmentioning
confidence: 99%
“…The literature is conflicting when trying to determine the capacity of ketamine to cause direct mast cell degranulation and histamine release. Some studies have demonstrated mast cell histamine release with ketamine use, although one such study was in a patient group with a history of allergy (asthma, hay fever, allergic rhinitis, atopic dermatitis) . Other studies have found that ketamine inhibits mast cell exocytosis and histamine release in animal models …”
Section: Discussionmentioning
confidence: 99%